The Military and Political Parties in Indonesia: The Ups and Downs of the Military's Political Role - Faridz Nurul Mubarok; Meisya Bella Puspita; Nur Lisma; Razmy Rakan Abdilla (GoResearch - Research & Publishing House, 2022)
This article examines the historical background of the emergence of the involvement of the Indonesian National Armed Forces (ABRI) in the socio-political field, specifically some of the reasons underlying government policies to involve ABRI in socio-political and economic activities. and the efforts of ABRI members themselves to contribute in this area. This research, which was conducted using a historical approach, concluded that ABRI's involvement in the socio-political sphere in Indonesia began after the democratic leadership of President Soekarno. Politically, Sukarno's reason for integrating the military into his government structure was the failure of civilian politicians to formulate a state ideology that was not approved by the parties in the Constituent Assembly. This failure is seen as endangering national political stability and threatening the country's integrity. Based on this, President Soekarno hired the military to balance civilian politicians in his government. Apart from the socio-political field, ABRI also has a socio-economic role.